Ethical Governance and Sustainability Disclosure: Pergeseran dari Symbolic Legitimacy Menuju Substantive Dignity - Arfianti, Rizka Indri (Jurnal Akuntansi, 2026)
Changes in corporate governance have marked a significant shift from rule-based compliance toward a commitment to sustainability. Sustainability disclosure is increasingly regarded as a measure of corporate integrity. In practice, however, sustainability reporting often remains symbolic, serving as a means for companies to project an image of social responsibility without being fully accompanied by substantive changes in internal practices. Drawing upon legitimacy theory and the distinction between symbolic and substantive actions, this article examines the limitations of governance approaches that rely excessively on legitimacy and formal compliance. Using a normative-critical conceptual paper approach, the study reconstructs the concept of ethical governance by positioning dignity as its foundational value. Dignity is understood as respect for the intrinsic worth of human beings, the environment, and future generations, thereby transforming sustainability disclosure from a mere reputational instrument into an expression of authentic moral commitment. Reflecting on the Indonesian context, including the practices of PT Unilever Indonesia Tbk, the article demonstrates that the transition from symbolic legitimacy to substantive dignity has significant implications for strengthening good corporate governance in emerging markets. This transformation underscores that the ultimate objective of ethical governance is no longer merely to secure social legitimacy, but to establish substantive dignity as the moral foundation of corporate governance. From an axiological perspective, sustainability disclosure is positioned as a manifestation of ethical responsibility that respects the dignity of human beings, the environment, and future generations, enabling governance to achieve not only compliance but also enduring institutional integrity.